Light intensity preference of juvenile pikeperch Sander lucioperca (L.) - Luchiari, Ana Carolina; de Morais Freire, Fulvio Aurelio; Koskela, Juha; Pirhonen, Juhani (Blackwell Publishing, 2006)
Light intensity preference of the pikeperch was tested in 1-m(2) tanks divided into four lateral compartments with a hole in the middle to allow the fish to move between compartments. Two experiments were carried out with both 0+ and 1+ pikeperch: one testing intensities from 25 to 300 lx and the other from 1 to 50 lx. Light preference was observed individually for 5 days at 8, 11, 14 and 17 h. on the first and fifth day, the preference was tested without differences in light intensity (control). In both experiments, both age groups showed preference for the lowest available light intensity. Preference for low light intensity in pikeperch may be related to innate activity and feeding behaviour and to avoidance of harmful effects of light. It is suggested that under aquaculture operations, pikeperch should be reared under very dim conditions.
Keywords: light intensity; preference; percid; pikeperch; Sander lucioperca